Anti-inflammatory and Anti-arthritic Activities of Aqueous Extract and Flavonoids from Tripodanthus acutifolius Leaves in Mice Paw Oedema - Ticona, Luis Apaza; Serban, Andreea Madalina; Ticona, Daly Apaza; Slowing, Karla (Planta Medica International Open, 2021)
Tripodanthus acutifolius, commonly known as Jamillo, is an herbal remedy used in traditional Andean medicine to treat joint problems, such as sprains, dislocations, and rheumatic pain. This study aimed to evaluate the in vitro and in vivo anti-inflammatory and anti-arthritic activity of the aqueous extract and isolated compounds of T. acutifolius. A bioguided phytochemical analysis based on NMR/MS was performed to identify the compounds of the aqueous extract from T. acutifolius. The anti-inflammatory and anti-arthritic activity were evaluated by measuring inflammatory parameters (TNF-α, C-reactive protein, and fibrinogen) in murine models. The chemical structure determination led to the identification of four flavonoids: (E)-2’,4’-dihydroxy-6’-methoxy-chalcone (1), 6,2’,4’-trimethoxyflavone (2), 5,3’,4’-trihydroxy-6,7,8-trimethoxyflavone (3), and 5,4’-dihydroxy-6,7,8-trimethoxyflavone (4). All compounds inhibited the production of TNF-α in the RAW 264.7 cell line, with IC50 values of 0.78, 1.43, 5.73, and 9.71 μM, respectively. In addition, all flavonoids decreased the levels of TNF-α, C-reactive protein, and fibrinogen at a concentration of 5 mg/kg in murine models. Our research shows that these compounds isolated from T. acutifolius have anti-inflammatory and anti-arthritic properties, providing scientific evidence for the traditional use of this plant species.
Keywords: Loranthaceae; Tripodanthus acutifolius; flavonoids; anti-inflammatory; anti-arthritic; TNF-α